Lo scienziato civico: una tipologia - Anzivino, Monia (Cambio. Rivista sulle Trasformazioni Sociali, 2020)
This study aims to contribute to our understanding of the factors and processes that lead scientists to engage in public communication. Using a large and national sample of academics from all Italian public universities and from all disciplines, this study identifies two different kinds of scientific communication activities and a typology of civic scientist on the basis of intensity and quality of engagement. Moreover, the study identifies some factors – discipline, age, gender and seniority – that contribute to define the different kinds of civic scientist and explain why for analysing the public engagement of academics, it is necessary to consider the different logic of actors involved in every kind of activities of communication, particularly in mass media activities and in local community activities.